The Role of Parents and Teachers in Communication Skill Development of Students with Intellectual Disability and Speech Delay (A Case Study at State Elementary School Junrejo 02 Batu). - Gita Ayu Swastika; Asep Sunandar; Henny Indreswari (Department of Special Education, 2021)
Parent and teacher hold an important role in children's communication development. Both of them have a time to spend with the children, parent almost take a whole time with their children in the home while teacher has a mean time in the school. The method used is qualitative methods of case study research. Collecting the data, doing an interview, observing, and documenting was used as main instrument. The steps to do a data analysis was reducing data, presenting data, and drawing the conclusions. Meanwhile, the data validation used the triangulation technique (technique triangulation and source triangulation) and member check. It showed that parent and teacher’s effort were to provide a two-way communication stimulus in the end.